Abdominal Tuberculosis with Malnutrition: A Case Report - Nuri Nurhasanah Sugandi; Shiela Stefani; Novie Kartika; Karina Febiani Widjaja; Marcellino Bulain; Medylin Duallo; Moses Arky Krisnanda; Nabila Cahya Putri; Nerissa Arviana Fuad; Revena Astanti Percunda (Medical Clinical Update, 2023)
Tuberculosis is caused by the bacterium Mycobacterium tuberculosis, 20% diagnosed as extrapulmonary TB. Abdominal becomes the most case of extrapulmonary TB. Patients with malnutrition are at risk of developing TB by 6-10 times. This study is aimed to learn more about the features of aabdominal TB with malnutrition in children.